RADT-45. EFFECT OF DIFFERENT RADIOTHERAPY TECHNIQUES ON HEMATOLOGICAL TOXICITY OF CRANIOSPINAL IRRADIATION. (9th November 2020) - Zhang, Yangqiong; Yang, Huajun; Deng, Guanhua; Luo, Rishun; Zhang, Ping; Cai, Linbo
Abstract: OBJECTIVE: To investigate the effect of different radiotherapy techniques on hematological toxicity of craniospinal irradiation. METHODS: A retrospective study involving changes in hematology during craniospinal irradiation were conducted. 79 patients were divided into observation group and control group. 36 patients in observation group received intensity modulated radiation therapy and 43 patients in control group received three-dimensional conformal radiotherapy. The prescribed dose of PTV in the two groups are 28.8-36 Gy, and the single dose are 1.6-2.0 Gy. The hematological toxicity changes and bone marrow suppression stage of the two groups of patients before, during and after radiotherapy were recorded and analyzed. RESULTS: 90% of patients showed different bone marrow suppression stage during and after radiotherapy. During radiotherapy, the toxicity of hemoglobin in the observation group was more serious than that in the control group (z=-2.272, p =0.023). After radiotherapy, the toxicity of hemoglobin and white blood cells in the observation group was more serious than that in the control group (z=-3.053, p =0.002; z=-3.163, p =0.002). CONCLUSION: We should closely observe the changes of hematological toxicity for craniospinal irradiation patient treated with IMRT and take corresponding preventive measures to avoid serious bone marrow suppression stage.